Cardioverter-related complications: observations from an institutional implantable cardioverter defibrillator registry. (24th May 2021) - Prepolec, I; Pasara, V; Ciglenecki, E; Putric Posavec, J; Bogdanic, JE; Matasic, R; Krpan, M; Lovric-Bencic, M; Pezo-Nikolic, B; Puljevic, M; Puljevic, D; Milicic, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Implantable cardioverter defibrillator (ICD) is gold standard therapy for primary and secondary prevention of sudden cardiac death (SCD) and ventricular tachyarrhythmias. While reducing arrhythmic mortality in patients with left ventricular dysfunction of various causes, inherited primary arrhythmia syndromes and after aborted SCD, these devices can have serious adverse effects including inappropriate shocks and device-related infection. Purpose: The aim of this study was to create an institutional ICD registry and to examine the major complications after ICD implantation. Methods: We analysed the data concerning all newly implanted ICDs in our institution from 2011 to 2017. All patients received periprocedural antibiotic prophylaxis according to relevant guidelines. Follow-up data was collected from hospital electronic medical records. Results: Total number of implanted ICDs was 507 (85.4% male, 57.6 ± 14.0 years-old) and mean follow-up was 34.3 ± 23.8 months. Major complications (infection, large haematoma/hemorrhage, lead displacement/dysfunction) occurred in 18 (3.6%) patients. In 9 (1.8%) cases patients were diagnosed with ICD infection (8 surgical wound/pocket infections and 1 confirmed endocarditis of the lead). Device was explanted in 5 cases (1.0%) while the rest were treated only with antibiotic therapy (empirically or according to swab/blood culture results). All of the infections were successfully resolved and no relapses were noted. Eventually, 3 of 5 devices were reimplanted. One death was recorded 5 month after the explanation. Second most common complication was lead displacement/dysfunction which occurred in 5 (1.0%) patients and was successfully repaired in all cases. Large haematoma and/or hemorrhage at the implantation site were present in 5 (0.8%) patients (2 required surgical revision and transfusion while 2 were managed by needle aspiration). Pneumothorax (2 cases, 0.4%) had to be drained in one patient. There was one case of subclavian vein thrombosis which was treated by anticoagulation. Conclusion: Despite appropriate antibiotic prophylaxis, the rate of ICD infections in our institution was relatively higher than the one reported in similar registries. The prevalence of other major complications, including lead dysfunction was quite low. Institutional registries could help monitor and plan actions to resolve ICD-related complications to improve patient outcomes.